The menace of narco power in Pakistan - Kukreja, Veena (2016)
This article seeks to analyse the menace of narco power in Pakistan. The 1980s, in the aftermath of the Afghan crisis, witnessed the rise of narco power in Pakistan. The narco power, which has assumed the role of one of the central pillars of the power structure in Pakistan, reveals triangular linkages and nexus between narcotics and politicians, army and ISI, and terrorism. Drug syndicates also run a parallel economy. The article also takes into account the relationship between narcotics and civil society to depict the menace of drug addiction and ethnic violence. With their penetration of state institutions, economy, and society, the narco barons today are the most formidable force threatening the government's authority, political stability, and the economic and social equilibrium of the society. - Reproduced.
Keywords: Drug abuse - Pakistan; Drug abuse